Analisis Fundamental dan Teknikal terhadap Harga Saham pada Perusahaan Utilitas dan Transportasi - Christina, Christina; Halim, Sulastri; Angrensia, Valentina; Pratania Putri, Arie (E-Jurnal Akuntansi; Vol 31 No 2 (2021)DO - 10.24843/EJA.2021.v31.i02.p19, 2021)
The purpose of this research is to known if fundamental and technical analysis could affect the price of stock. Furthermore each of analysis have several factor to determine the stock price, as for fundamental analysis we will use current ratio, DER, and ROA while for the technical analysis we will use IHSG and trading volume. From the population of 69 company we pick 18 sample that suit the analysis, for the regression it will use multiply 5 because of the independent variabel. According to the partial research, there are only two factor that have significant impact to the price of stock, it is DER And ROA, as for the rest of the factor it don’t really affect the price. Simultaneously the five variabel shown the effect to the stock price according to result of adjused r square amount of 29.1% . From the variation of stock price according to the variabel such as CR, DER , ROA. IHSG and trading volume, while the rest 70.9% affected by other factor such as company asset turnover, price earning ratio and price book value. Keywords: Current Ratio; Debt to Equity Ratio; IDX Composite; Return On Asset; Stock Price; Trading Volume.